2016
DOI: 10.18632/oncotarget.14410
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical profiling of receptor tyrosine kinases, MED12, and TGF-βRII of surgically resected small cell lung cancer, and the potential of c-kit as a prognostic marker

Abstract: The limited number of available treatments for patients with small-cell lung cancer (SCLC) has prompted us to further investigate the biology of SCLC by molecular profiling. We collected formalin-fixed paraffin-embedded tumor samples from 127 patients with SCLC, who had undergone surgery at 16 institutions between January 2003 and January 2013, and analyzed the association between disease-specific survival and protein expression of c-kit, c-Met, epidermal growth factor receptor, human EGFR-related 2, vascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…Thus, the functional link of MED12 and TGF-βR2 only exists in the NSCLC subtype of lung cancer, and MED12 and TGF-βR2 should not be considered as universal biomarkers for all types of lung cancer. 43 We have demonstrated that higher levels of MED12 and CARM1 predict a better response to chemotherapeutics in patients with breast cancer. 31 Methylation of MED12 by CARM1 renders cells sensitive to 5-fluorouracil, but not to the receptor tyrosine kinase inhibitors, in vitro and in vivo, suggesting that the mechanism of mediating drug response in breast cancer cells is different from TGF-βR2-mediated pathways in NSCLC.…”
Section: Med12 In Drug Resistancementioning
confidence: 87%
See 1 more Smart Citation
“…Thus, the functional link of MED12 and TGF-βR2 only exists in the NSCLC subtype of lung cancer, and MED12 and TGF-βR2 should not be considered as universal biomarkers for all types of lung cancer. 43 We have demonstrated that higher levels of MED12 and CARM1 predict a better response to chemotherapeutics in patients with breast cancer. 31 Methylation of MED12 by CARM1 renders cells sensitive to 5-fluorouracil, but not to the receptor tyrosine kinase inhibitors, in vitro and in vivo, suggesting that the mechanism of mediating drug response in breast cancer cells is different from TGF-βR2-mediated pathways in NSCLC.…”
Section: Med12 In Drug Resistancementioning
confidence: 87%
“…In contrast to NSCLC, MED12 function seems to be intact in small‐cell lung cancer (SCLC), in which no association has been found between the expression of MED12 and TGF‐βR2 or with clinical variables such as overall survival. Thus, the functional link of MED12 and TGF‐βR2 only exists in the NSCLC subtype of lung cancer, and MED12 and TGF‐βR2 should not be considered as universal biomarkers for all types of lung cancer …”
Section: Med12 In Drug Resistancementioning
confidence: 95%
“…We included patients with primary SCLC who had undergone complete surgical resection of a primary lung tumor between January 2003 and January 2013 at institutions participating in either the Fukushima Investigative Group for Healing Thoracic Malignancy (FIGHT) or the Hokkaido Lung Cancer Clinical Study Group Trial (HOT) . Patients were centrally re‐reviewed for a confirmed pathological diagnosis of pure SCLC or combined SCLC, according to the 2004 World Health Organization classification .…”
Section: Methodsmentioning
confidence: 99%
“…GUCA2A was down-regulated in Subtype-2 samples, many studies on GUCA2A indicates its role as a biomarker in diagnosing cancer. Aberrantly expressed GUCA2A can be a candidate Lou, Jianzhong Wu, 2019) Under expression of TGFBR2 in Subtype-1 samples is associated with poor prognosis, and TGFBR2 is also associated with poor prognosis in cervical cancer (Yang et al, 2017;Yokouchi et al, 2017). CENP-F, a cell cycle-regulated centromere protein, has been shown to affect numerous tumorigenic processes, increased expression of CENP-F in subtype-1 correlates with poor survival.…”
Section: Discussionmentioning
confidence: 99%